APLIKASI PERHITUNGAN INTERPOLASI NEWTON DENGAN BORLAND DELPHI 5.0. - Ni Wayan Parwati Septiani (Faktor Exacta, 2011)
This Application program is a form of visualization calculation application of  Newton Interpolation using Borland Delphi 5.0. This visual design from Borland Delphi 5.0. make easier for programmers to create an atractive user interface without typing any codes. Besides an atractive user iterface, this applications perform Newton Interpolation calculations more quickly and efficiently. Key Words: interpolation, borland, application